2017
DOI: 10.1055/s-0037-1606644
|View full text |Cite
|
Sign up to set email alerts
|

Probable Association of Hearing Loss, Hypertension and Diabetes Mellitus in the Elderly

Abstract: Introduction  The aging process causes changes in body structure in a continuous manner, and contributes to clinical disorders. Life expectancy is increasing, especially in developing countries. Objective  To assess the prevalence of hearing loss and its possible association with hypertension and diabetes mellitus (DM) in the elderly. Methods  A cross-sectional study with 519 elderly individuals aged over 60 years who underwent an audiological evaluation (pure tone audiometry), and answered a comorbidity que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
2
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 19 publications
4
16
2
14
Order By: Relevance
“…The age group was categorized in the present study because another paper from our research group with the same population showed a significant difference between HL and the age groups. 2 However, the data did not demonstrate the same association with postural balance. Possibly, the process of sensory reweighting has actuated by reallocating the essential sensory information for the less affected body system.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The age group was categorized in the present study because another paper from our research group with the same population showed a significant difference between HL and the age groups. 2 However, the data did not demonstrate the same association with postural balance. Possibly, the process of sensory reweighting has actuated by reallocating the essential sensory information for the less affected body system.…”
Section: Discussionmentioning
confidence: 76%
“…In a Brazilian study with a total of 498 elderly subjects with a median age of 69 years were evaluated, sensorineural hearing loss (SNHL) was more prevalent (66.26%) of most frequently with bilateral hearing loss of 91.56% and 26.50% with mild degree. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Os estudos selecionados evidenciaram a DM e a HAS como possíveis fatores de risco para o desenvolvimento da perda auditiva [10][11][12] . Pacientes com DM possuem um risco maior de desenvolver uma perda auditiva 12 do tipo sensorioneural 11,12,14,16 . Alguns estudos destacaram que o tabagismo 12 , o elevado Índice de Massa Corpórea (IMC) 10 , a exposição ao ruído e a idade elevada 14 também podem ser determinantes para a perda auditiva (Tabela1).…”
Section: Resultsunclassified
“…Os artigos selecionados para essa revisão foram os que atenderam aos seguintes critérios de inclusão: indivíduos com perda auditiva em decorrência de doenças crônicas não transmissíveis como a diabetes e hipertensão; idiomas português, inglês e espanhol sem restrição de localização, porém com restrição de período de publicação, sendo incluídos estudos publicados de 2014 a 2019. , enquanto outros três estudos realizaram sua pesquisa apenas com a população idosa (idade ≥ a 60 anos) 11,14,17, . O número de sujeitos selecionados para as pesquisas variou de 80 a 37.773 [10][11][12][14][15][16][17][18] , sendo que uma delas não mencionou o número de indivíduos inclusos 13 . Em relação ao sexo dos participantes, destaca-se o feminino 10,13,14,16 porém, não foram todos os autores que mencionaram o sexo dos indivíduos estudados 11,17,18 .…”
Section: Critérios De Seleçãounclassified
See 1 more Smart Citation